Resistência e denúncia no discurso de Carolina Maria de Jesus na obra Quarto de despejo - Andrade, Genilma Dantas (2024)
Using the foundations of French Discourse Analysis, this research examines the process of subjectivation and canonical literary discursivity in Carolina Maria de Jesus. Its main objective was to carry out a discursive analysis of the work Quarto de Despejo: diário de uma favelada (2001), which had great repercussions and success in the publishing market in the 1960s. I specifically sought to analyze the author's discourse as the fruit of denunciation and resistance to her condition as a slum dweller. Our specific objectives, in turn, are developments of the guiding question. They are: a) to situate the discourse under investigation historically, considering its conditions of production; b) to identify, in the discourses under analysis, the construction of the author's subjectivity; c) to observe, in the discursive practices, traces of political activism and resistance. In order to achieve the objectives of this work, the corpus consisted mainly of discursive sequences taken from the work Quarto de despejo: diário de uma favelada, written between 1955 and 1960. The effects of resistance mean that this literary production can be recognized as a literature of social confrontation and, finally, contributes to reflecting on the absence of black authors, raising some questions about silencing. This study is based on authors from French Discourse Analysis, such as Pêcheux (1979, 1990, 1995, 1996, 1997, 2014); Orlandi (1998, 1996, 2005, 2012), although there are also contributions from other authors, such as Bauman (1998, 2001, 2003) on identity, Mussalin (2003), Carvalho (2012), among others. The analysis shows that Carolina Maria de Jesus' writing is an act of denunciation and resistance because, as well as revealing the chaotic situation she and other favela residents were going through, it breaks with an imaginary formation of a white, middle-class, highly educated, intellectual author. By discussing the "hunger for writing and the writing of hunger", through the weaving of the poetic, the subjectauthor pays attention to the formation of a literature of denunciation and social confrontation. Furthermore, by materializing meanings, this subject-author works the interdiscourse in the intradiscourse in order to build his writing project, bringing other spaces to our literature, from its non-place in the historiography of Brazilian literature. This approach has allowed us to understand a little more about the condition of black women and how they fit into literary discourse at a given historical moment.